Effect of Delay in Operative Treatment on the Range of Motion in Supracondylar Humerus Fracture - Junaid Khan, Riaz Ahmed, Rahman Rasool Akhtar, Kanza Batool, Hashim Riaz (Journal of Rawalpindi Medical College, 2017)
To determine the relationship of delay in management of supracondylar fracture of humerus with reduced mobility of the joint. Methods: In this descriptive study patients with isolated fracture of supracondylar of humerus without any associated trauma, were included. They were classified into groups according to Gartlands’ classification based on antero-posterior and lateral view Xrays of the affected elbow joint. Patients were called for follow up 4,8 and 12 weeks after removal of backslab and Kirschner wires. Results: Mean age of presentation for fractures of supracondylar of humerus was 5.67±2.064 years with fracture occurring predominantly in males. Out of the 32 patients who sustained Gartland type III fractures, only 8(25%) patients were managed by closed reduction and internal fixation. In 28(75%) patients, open reduction and internal fixation had to be done. Mean delay time for treatment in type-I and type-II fractures was 2.86±2.25 and 2.56±1.42 days respectively. Gartland type-III injuries had a delay between injury and surgery of 4.88±2.95 days. Range of motion was more reduced in flexion angle as compared to extension, supination and pronation. Conclusion: An inverse relation was found between delay in presentation and range of motion. Increase in delay to seek optimal treatment is associated with a reduction in range of movement at the supracondyle of humerus. In Gartland type III fractures, open reduction had to be done to achieve satisfactory results in most of the patients who presented after a delay of more than 3 days. Follow up of the patients showed an improvement in mobility of the joint in the postoperative period but role of physiotherapy in achieving maximum mobility has not been determined yet